The Role of Augmented Reality as a Learning Tool in Facilitating Understanding of Interval Concepts in Real Analysis - Siregar, Anisa Rahmadani; Arsandy, Qory Septiani; Simanullang, Michael Christian (JPMI (Jurnal Pendidikan Matematika Indonesia), 2025)
Learning mathematics at the college level often faces challenges in understanding abstract concepts, one of which is the concept of intervals in real analysis. Augmented Reality (AR) is an innovative technology that can be used as a learning aid by presenting interactive visualizations in three dimensions. This study aims to explore the role of Augmented Reality in facilitating students' understanding of the concept of intervals. The research method used is a qualitative approach with a case study design conducted on students of the mathematics education study program. Data were collected through tests and analyzing students' understanding of the concept of intervals after using Augmented Reality-based learning media. The results showed that Augmented Reality was able to improve students' understanding of the concept of intervals, with a success rate of 75% in understanding the types of intervals and interval representations, and 100% in understanding the concept of nested intervals. These findings indicate that the use of Augmented Reality in mathematics learning can increase students' interest and motivation and help them understand abstract concepts more deeply. Therefore, the application of Augmented Reality as an interactive learning media is recommended to support the learning process in college, especially in real analysis courses.Peran Augmented Reality Sebagai Alat Bantu Pembelajaran Dalam Memfasilitasi Pemahaman Konsep Interval Pada Analisis RealABSTRAKPembelajaran matematika di tingkat perguruan tinggi sering kali menghadapi tantangan dalam memahami konsep abstrak, salah satunya adalah konsep interval dalam analisis real. Augmented Reality (AR) merupakan teknologi inovatif yang dapat digunakan sebagai alat bantu pembelajaran dengan menghadirkan visualisasi interaktif dalam bentuk tiga dimensi. Penelitian ini bertujuan untuk mengeksplorasi peran Augmented Reality dalam memfasilitasi pemahaman konsep interval mahasiswa. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan desain studi kasus yang dilakukan pada mahasiswa program studi pendidikan matematika. Data dikumpulkan melalui tes dan menganalisis pemahaman mahasiswa terhadap konsep interval setelah menggunakan media pembelajaran berbasis Augmented Reality. Hasil penelitian menunjukkan bahwa Augmented Reality mampu meningkatkan pemahaman mahasiswa terhadap konsep interval, dengan persentase keberhasilan 75% dalam memahami jenis interval dan representasi interval, serta 100% dalam memahami konsep interval bersarang. Temuan ini mengindikasikan bahwa penggunaan Augmented Reality dalam pembelajaran matematika dapat meningkatkan ketertarikan dan motivasi mahasiswa serta membantu mereka memahami konsep abstrak secara lebih mendalam. Oleh karena itu, penerapan Augmented Reality sebagai media pembelajaran interaktif direkomendasikan untuk mendukung proses pembelajaran di perguruan tinggi, khususnya dalam mata kuliah analisis real.Kata Kunci :Augmented Reality; Interval; Pemahaman